A ludicidade nas aulas de Ciências nos anos finais do Ensino Fundamental - Bárbara Elisa Santos Carvalho Luz (2021)
In the educational scope, ludicity is closely linked to Preschool, a period in which games, games and so-called fun activities are part of everyday life and are naturally sought after and idealized by children. However, with the advance of schooling, especially in the final years of Middle School, the ludic loses space in educational practices as it distances itself from the seriousness and formality that guide the forms of organization of the school. After scoring and discussing the polysemy inherent to ludic in the educational context, it was decided to work with the concept of ludicity and the existence of clashes between instrumentality and essentiality related to it was assumed. Instrumental ludicity understand ludic as a tool to facilitate learning and essential ludicity considers that ludic education transcends the rationalist bias that is so striking in current educational processes and understands ludic as a generator of affection and emotions. The motivation for the investigation that supported this thesis were personal questions about the interlacement between ludicity and Science Education, from which it was found that the theme of ludicity has not received, so far, many research efforts within this field. In order to contribute to this scenario, ludicity in Science classes in the final years of Middle School was taken as an object of study in order to investigate its characteristics, movements triggered by it and how it manifests and operates. Through a methodological bricolage between elements of educational ethnography and foucaultian-inspired discourse analysis, different ways of manifesting ludicity in Science classes were perceived and that they depend on the existence of a ludic teaching condition. It was also observed that the ways in which ludicity manifested itself in accompanied classes were not restricted to games, scavenger hunts and play, and the ways in which it operated produced a series of effects on students, on the relationships between subjects and in the school environment. From this, the developed thesis is that the existence of a ludic teaching characteristic enables manifestations of ludicity in Science classes in the final years Middle School. These manifestations characterize the ludicity in these classes as a ludic ambience crossed by power relations that produce expected and unexpected effects by the teacher.